TINJAUAN SOSIOLOGI HUKUM TERHADAP PASAL 1 AYAT (1) UNDANG-UNDANG NO. 13 TAHUN 2008 TENTANG PENYELENGGARAAN IBADAH HAJI - Muhammad, Nashih (Jurnal Ilmiah Citra Ilmu, 2021)
Hajj is an obligation for all Muslims who are able to carry it out. Muslims in Indonesia have been recorded since the Dutch government had performed the pilgrimage until after Indonesia's independence. However, the government's presence in seeking every citizen who performs the pilgrimage at the beginning of the independence period is still very minimal. Pilgrimage is a complex worship because it involves many things in it. Starting from the education of Hajj rituals, travel services, accommodation involving two countries. It was only in 2008, 63 years after Indonesia's independence, that a law was issued that provides legal certainty and protection for pilgrims in Indonesia. What is the background of the birth of Law no. 13 of 2008 in terms of the sociology of law?. This research is a qualitative research that is descriptive-analytical with a literature review method. The result of this research is the emergence of Law no. 13 of 2008 can be understood as a social phenomenon of the Indonesian Muslim community.